The role of social actors in the municipalities of Guatape-Peñol seen from the sustainable tourism paradigm - Giraldo Velásquez, Claudia María (2017)
In this research it has been determined the role of social actors –whichare understood as residents,entrepreneurs, city managers, tourists and different entities working on issues related to the sustainabledevelopment of tourism in the municipalities of Guatape y Peñol, located in Antioquia (Colombia). Theperformances of these actors have been evaluated in relation to environmental, socio-cultural and economicissues.